Genetic characterization of nodular worm infections in Asian Apes - Yalcindag, Erhan; Stuart, Peter; Hasegawa, Hideo; Streit, Adrian; Doležalová, Jana; Morrogh-Bernard, Helen; Cheyne, Susan M; Nurcahyo, Wisnu; Foitová, Ivona (Scientific reports, 2021)
Parasitic nematodes of Oesophagostomum spp., commonly known, as 'nodular worms' are emerging as the most widely distributed and prevalent zoonotic nematodes. Oesophagostomum infections are well documented in African non-human primates; however, the taxonomy, distribution and transmission of Oesophagostomum in Asian non-human primates are not adequately studied. To better understand which Oesophagostomum species infect Asian non-human primates and determine their phylogeny we analysed 55 faecal samples from 50 orangutan and 5 gibbon individuals from Borneo and Sumatra. Both microscopy and molecular results revealed that semi-wild animals had higher Oesophagostomum infection prevalence than free ranging animals. Based on sequence genotyping analysis targeting the Internal transcribed spacer 2 of rDNA, we report for the first time the presence of O. aculeatum in Sumatran apes. Population genetic analysis shows that there is significant genetic differentiation between Bornean and Sumatran O. aculeatum populations. Our results clearly reveal that O. aculeatum in free-ranging animals have a higher genetic variation than those in semi-wild animals, demonstrating that O. aculeatum is circulating naturally in wildlife and zoonotic transmission is possible. Further studies should be conducted to better understand the epidemiology and dynamics of Oesophagostomum transmission between humans, non-human primates and other wild species and livestock in Southeast Asia.
Keywords: Animals; Indonésie; Ape Diseases; DNA, Helminth; Oesophagostomiasis; prevalence; Pongo pygmaeus; zvířata; feces; Feces; DNA helmintů; Prevalence; Indonesia; ezofágostomiáza; Hylobates; Oesophagostomum; nemoci lidoopů